Chemical Composition of Artocarpus communis (Breadfruit) Seed flour as Affected by Processing (Boiling and Roasting) - Okorie, S.U. (Pakistan Journal of Nutrition, 2010)
Artocarpus communis (Breadfruit) seed flour was subjected to boiling and roasting to determine their effects on the chemical composition. Proximate composition showed a significant difference (p>0.05) in the raw and processed flour samples. The moisture content was lowest (14.77%) in the roasted A. communis seed flour and highest (24.08%) in the boiled seed flour. Percentage ash, fat and protein were highest (3.66, 3.74 and 4.67%) in the raw while ash and fibre contents were least (2.75 and 1.81%), respectively in the boiled flour. Carbohydrate was highest (87.29%) in the boiled and least (85.60%) in the raw. Boiling and roasting indicated that the vitamin C content and the mineral contents were significantly higher in the raw A. communis seed flour. The effects of boiling and roasting with regards to loss and retention of the nutrients differed significantly (p>0.05), with only the roasting retaining more of the nutrients than boiled seed flour. Sodium and potassium contents of boiled (0.27 and 0.75 mg/L), respectively and roasted (0.34 and 0.78 mg/L, respectively) A. communis seed flours compared well (p<0.05) with the raw (0.37 and 0.83 mg/L, respectively).